Block Tridiagonal Solvers on Heterogeneous Architectures - Valero-Lara, P.; Pinelli, A.; Favier, J.; Matias, M. P. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
Modern multi-core and many-core systems offer a very impressive cost/performance ratio. In this paper a set of new parallel implementations for the solution of linear systems with block-tridiagonal coefficient matrix on current parallel architectures is proposed and evaluated: one of them on multi-core, others on many-core and finally, a new heterogeneous implementation on both architectures. The results show a speedup higher than 6 on certain parts of the problem, being the heterogeneous implementation the fastest.